THE IMPORTANCE OF HAND WASHING IN THE HOSPITAL ENVIRONMENT - Ana, Claudia (2023)
Knowing that hospitals are institutions to promote healing and care for citizens who need assistance to restore their health. It is essential that the Health Institution promotes humanized, safe and correct care in accordance with duly standardized procedures and standards to obtain an effective result. However, we know that this is not the reality we experience. We still have high rates of hospital infections, which leads us to reflect on the basic rules of care necessary for the essential contribution to combating hospital infections. It was between 1818/1865 that the Hungarian doctor Ignes Philip Semmelweis came across a high increase in the rate of puerperal fever, he highlighted and postulated the obligation of hand hygiene with chlorinated solution between care for each patient, he noted the enormous reduction in the rate of maternal mortality. Thus beginning an essential procedure for health care and assistance. Despite the greater focus on the transmission of diseases in hospital environments and in our society in general, the practice of hand hygiene still acts precariously. It was in 1975 that guides and guidelines began to emerge regarding the practice of correct hand hygiene. Techniques were developed and standardized through COREN. These being: simple, antiseptic, surgical and pre-operative hygiene. Hand hygiene was one of the globally effective ways to prevent the spread of the recent Pandemic we have suffered. COVID 19. And much of this spread was due to a lack of information/awareness among the large population, where the practice of this procedure (which must be carried out daily among homes) was not completely understood. Practice is essential for everyday life, and can be replaced by the use of alcohol gel in the absence of water and soap (as long as there is no dirt on the hands. In a hospital environment, hand hygiene procedures are defined for each care procedure, depending on the The nursing team continuously observes them, making the team aware that correct hygiene ensures the health of professionals, patients and the Hospital Environment, reducing contagion. (promoted in the institution occupies a bed, he is administered medicines that could treat another patient). And mainly and not death. Basic, cheap and effective practice as long as it is correctly carried out. In this way, it is highlighted that Continuous Education campaigns for Awareness of the entire population is required to discuss the topic “hand hygiene”, not only as a rule and mandatory in the Hospital Environment, essential to promote health in the units. But also in society in general.